Kadar Asam Klorogenat (CGA) Dalam Biji Kopi Arabika (Coffea Arabica) Asal Wamena, Papua - Mangiwa, Septiani; Futwembun, Alowisya; Awak, Puteri M. (Hydrogen: Jurnal Kependidikan Kimia, 2015)
Chlorogenic acid (CGA) is one of chemical compound in coffee and class of polyphenolic compounds that have activity as antioxidant.Â This study aims to determine the CGA contain in Arabica coffee beans from Wamena regency of Jayawijaya, Papua.Â Coffee beansÂ were roasted by three roasting temperature i.e. 75, 150 and 2250 C while unroasted one was used as controls. Extraction was performed by soxhletation using metanol asÂ a solvent for 5 hours. Separation andÂ CGAcontent were determined using HPLC uses C-18 column, 150 mm length, 4,6 mm in diameter, with metanol-fosfat buffer 10 mM pH 2,6(30:70) as eluent, flow rate of 1 mL/minutes, injection volume of 20 ÂµL and measured by spectrophotometer UV-Vis in 329 nm. The result of the study shows the CGAcontent Â in treated beans with temperature roasting of 75, 150 and 2250C Â respectively were 6,93 ; 9,33 and 7,12 % while the unroasted one was Â 7,73 %. The lowest CGA content was found in coffee beans roasted in 750C while the highest in 1500 C.